A negociação no Direito Administrativo: uma perspectiva sobre o acordo de leniência - Ribeiro, Manoela Barbosa Machado (2018)
Negotiation is an important part of the study of law. However, some areas of law are more resistant to the use of negotiation, among them the Administrative Law, where the pillars of supremacy and unavailability of the public interest can serve as a hasty excuse to discourage the use of negotiation. The evolution in the form of management by the Public Administration is leading to overcome this understanding, after all, even in this area of law, it is possible to harmonize public interests through the negotiation process. The Administration gradually began to prioritize consensus, agreements and negotiation. Considering the evolution and expansion of the use of negotiation by the Public Administration, with the arise of the Federal Law n. 12.846/2013, another important example of its negotiating practice has been regulated, the so-called leniency agreements. However, even though the leniency agreement is an example of the use of these new negotiating concepts, the uncertainties that permeate it, especially regarding the extent of the freedom granted to the Public Administration, which includes the freedom to celebrate the agreement and the freedom to apply the sanctions that result from it, has created much controversy, disputes and insecurity, which puts at risk the survival of this institute. Therefore, this work seeks to analyze the leniency agreement as a result of the negotiation process, its limits and consequences